2008
DOI: 10.1590/s0103-507x2008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que tornam estressante o trabalho de médicos e enfermeiros em terapia intensiva pediátrica e neonatal: estudo de revisão bibliográfica

Abstract: Objectives: Bibliographic review on occupational stress and burnout presence in physicians and nurses that work in pediatric and neonatal intensive care units. Methods: The articles were selected from the MedLine, LILACS and Sci-Elo data base using the key words: stress, burnout, physicians, nursing, intensive care unit, pediatric intensive care unit and neonatal intensive care unit. The studied period was from 1990 to 2007. Results: Health professionals who work in pediatric and neonatal intensive care units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
36

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
2
10
0
36
Order By: Relevance
“…Sabe-se que a UTI é um ambiente de trabalho que gera tensão e estresse, motivados, em especial, pela exposição ao risco de morte e oscilação frequente entre fracasso e sucesso 26 . Vale ressaltar que os profissionais do serviço de pronto atendimento não apresentaram altos níveis nas subescalas.…”
Section: Discussionunclassified
“…Sabe-se que a UTI é um ambiente de trabalho que gera tensão e estresse, motivados, em especial, pela exposição ao risco de morte e oscilação frequente entre fracasso e sucesso 26 . Vale ressaltar que os profissionais do serviço de pronto atendimento não apresentaram altos níveis nas subescalas.…”
Section: Discussionunclassified
“…These studies show the repercussions of organizational factors on the mental and physical health of physicians and nurses who work in pediatric and neonatal ICUs such as: burnout, psychological disorders generating professional stress, changing cortisol levels and salivary amylase due to excessive noise, relationship difficulties within the team, patients and family members. It is worth noting that two recent national studies (10)(11) that evaluated intensivist nurses and physicians showed that occupational stress led to dissatisfaction with work, affected physical health, mobilized feelings of suffering originating from relationships with patients and family members, team work, turnover, absenteeism and the high technology present in these units, in addition to the prevalence of burnout in physicians.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, some studies (7)(8)(9)(10)(11)(12)(13) show the outcomes of organizational aspects on the physical and mental health of physicians and nurses working in pediatric and neonatal ICU such as|: burnout, psychological changes generating professional stress, alteration of salivary cortisol and amylase due to excessive noise, difficulties of team relationships with family members and patients. Two recent Brazilian studies that assessed intensivist nurses and physicians are also noteworthy.…”
Section: Introductionmentioning
confidence: 99%